Innovation in creative technology : academic and creative economy - Khairul Azhar Mat Daud; Abu Hassan Hasbullah; Ahmad Rasdan Ismail; Nik Zulkarnaen Khidzir; Suriatini Ismail (Universiti Malaysia Kelantan, 2014)
The existing of National Creative Industry Policy existence is proof that government is serious in its efforts to uplift the creative industry to a higher level. In order to ensure the government’s aspiration can be realised, national education is needed to play its role. Education curriculum which is parallel to the National industrial policy should be introduced. It can be seen that, Faculty of Creative Technology and Heritage is the only faculties in this country that supports this aspiration. Additionally, FTKW is expected to become a creative technology-based learning centre which is extremely relevant to the needs of the society and economic development in 21st century